Market Structure and Double Bottom Line Commitments: Are They Aligned in Indian Microfinance Industry?. (April 2019) - Pati, Ambika Prasad
This article empirically examines the structure of Indian microfinance market and assesses its relationship with the double bottom line commitments of microfinance institutions. The market is found to be monopolistic in nature with high degree of concentration at the top, though a slow tendency of increased competition during the post-Andhra Pradesh crisis period is observed. Market share is found to be negatively related to average loan size and positively with number of active borrowers, indicating social commitments but with no relationship with profitability and sustainability. However, the post-crisis period portrays a departure from their social mission.